103 THE PEROXISOMAL PROLIFERATOR-ACTIVATED RECEPTOR-ALPHA REGULATORY PATHWAY IS ACTIVATED IN PATIENTS WITH SEVERE IDIOPATHIC DILATED CARDIOMYOPATHY. (1st January 2005) - Robinson, P. F.; Tsvetkova, T. O.; Nunley, K. R.; Calalb, M. B.; Sucharov, C. C.; Bristow, M. R.
Abstract : Background: Peroxisome proliferator-activated receptor α (PPAR-α) is a ligand-activated transcription factor that controls the expression of genes involved in cellular fatty acid (FA) import and oxidation. Transgenic mice over-expressing PPAR-α develop a dilated cardiomyopathy. Animal studies have shown the PPAR-α regulatory pathway is deactivated in pathologic cardiac hypertrophy and hypoxia, two circumstances characterized by reduced FA oxidation and increased dependence on glucose as a fuel source. Data in humans has been conflicting. There is evidence that indicates the failing human heart exhibits metabolic abnormalities in the form of a shift towards fatty acid metabolism away from glucose. Hypothesis: PPAR-α regulatory pathway is activated in patients with heart failure from idiopathic dilated cardiomyopathy, resulting in increased FFA oxidation. Methods: Total protein and RNA were prepared from human left ventricular tissue from hearts of patients with end-stage idiopathic dilated cardiomyopathy without diabetes mellitus, beta blocker treatment, or LVAD placement (N=10) at the time of transplantation and from control nonfailing donor hearts (N=10). PPAR-α receptor protein abundance was measured by Western blot analysis using a PPAR-α monoclonal antibody. Protein normalization was done using a standard Amido-Schwartz assay. PPAR-α mRNA expression was measured by ribonuclease protection assay (RPA). RPA results were normalized against GAPDH. Results: Western blot analysis of the PPAR-α protein content showed a significant increase in the failing hearts as compared to the control hearts (normalized mean ± SEM 167.1 ± 20.66 vs. 99.99 ± 13.69, p=0.01). mRNA analysis showed no significant difference in PPAR-α mRNA abundance between the two groups (64.40 ± 3.32 vs.75.48 ± 5.39, p = NS). Conclusions: PPAR-α protein abundance is increased in the failing human heart, indicating that this regulatory pathway may be activated in patients with severe idiopathic dilated cardiomyopathy. This activation appears to occur via a post-transcriptional modification. Methods: Total protein and RNA were prepared from human left ventricular tissue from hearts of patients with end-stage idiopathic dilated cardiomyopathy without diabetes mellitus, beta blocker treatment, or LVAD placement (N=10) at the time of transplantation and from control nonfailing donor hearts (N=10). PPAR-α receptor protein abundance was measured by Western blot analysis using a PPAR-α monoclonal antibody. Protein normalization was done using a standard Amido-Schwartz assay. PPAR-α mRNA expression was measured by ribonuclease protection assay (RPA). RPA results were normalized against GAPDH. Results: Western blot analysis of the PPAR-α protein content showed a significant increase in the failing hearts as compared to the control hearts (normalized mean ± SEM 167.1 ± 20.66 vs. 99.99 ± 13.69, p=0.01). mRNA analysis showed no significant difference in PPAR-α mRNA abundance between the two groups (64.40 ± 3.32 vs.75.48 ± 5.39, p = NS). Conclusions: PPAR-α protein abundance is increased in the failing human heart, indicating that this regulatory pathway may be activated in patients with severe idiopathic dilated cardiomyopathy. This activation appears to occur via a post-transcriptional modification.